Quantifying water productivity using seed priming and micro irrigation in wheat - Meena, Raj Pal; Sharma, Ramesh Kumar; R, Sendhil; Tripathi, Subhash Chander; Chander, Subhash (Journal of Cereal Research, 2018)
Field studies were conducted during the four Rabi seasons (2011-12 to 2014-15) to investigate the impact of seed priming and micro irrigation on crop establishment, growth, productivity, and water productivity in wheat under different moisture regimes. Results indicated that sprouted seed (5830 kg ha-1) and primed seed (5766 kg ha-1) produced significantly higher grain yield in comparison to un-primed seeds (5416 kg ha-1). The germination was quick in the primed and sprouted seeds relative to non-primed seeds resulting in a better crop establishment and higher yield under optimum, sub-optimum and dry soil conditions. Irrigation method treatments viz., check basin, drip, sprinkler and drip + rainport showed that the grain yield was highest in the drip + rainport. Water productivity was highest in drip method of irrigation (1.61 kg m-3 ) followed by drip + rainport method (1.60 kg m-3 ) with a maximum mean productivity of 5539 kg ha-1 . Around 600 m3 ha-1 has been saved using seed priming thus reducing the cultivation cost by 382/ha. Among the micro irrigation techniques, water saved was highest in drip followed by sprinkler and drip + rainport. The study suggests for adoption of drip and seed priming to take advantage of yield enhancement as well as cost reduction through reduced utilisation of water.